2020
DOI: 10.2147/tcrm.s243462
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hypophosphatemia Associated with Intravenous Iron Therapies for Iron Deficiency Anemia: A Systematic Literature Review</p>

Abstract: Background: Iron deficiency anemia (IDA) is a prevalent yet underdiagnosed condition with a significant impact on quality of life. Oral iron supplementation is often poorly tolerated or yields inadequate response, requiring the use of intravenous iron (IVI) in some patients. Administration of certain IVI preparations has been associated with decreases in serum phosphate levels and clinically significant hypophosphatemia, which has been reported to lead to adverse events including serious fatigue and osteomalac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 58 publications
3
58
0
1
Order By: Relevance
“…The effect of serum PO 4 3− lowering following administration of FCM has been frequently observed in interventional, observational, and retrospective studies [20,[36][37][38][39][40][41][42]. This effect has been seen at 2 weeks following FCM administration, and persistence of laboratory HP at Weeks 5 and 6 has been noted [39][40][41].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The effect of serum PO 4 3− lowering following administration of FCM has been frequently observed in interventional, observational, and retrospective studies [20,[36][37][38][39][40][41][42]. This effect has been seen at 2 weeks following FCM administration, and persistence of laboratory HP at Weeks 5 and 6 has been noted [39][40][41].…”
Section: Discussionmentioning
confidence: 91%
“…Given that fully functional kidneys have the capacity to modulate excess phosphate in the blood, compromised kidneys (as with CKD patients and heart failure patients with eGFR < 65 mL/min/1.73 m 2 ) may have a reduced capacity for renal excretion and therefore are hyperphosphataemic and are at a decreased risk of developing HP following FCM treatment [20]. It has been noted elsewhere that patients with gynaecological causes of iron-deficiency anaemia tend to have higher HP rates, which may explain the higher-than-anticipated incidence of HP following their treatment with FCM [40,42]. Chronic HP has a number of different potential aetiologies, including genetic mutations, altered immunity, tumour induction, and renal disease [57].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the heterogeneous methodology of the studies and the different definition of hypophosphatemia, FCM is the form of IV iron most frequently associated with this complication. In a recent systematic literature review hypophosphatemia associated to IV iron therapies was reported in 19 randomized control trials ( Glaspy et al, 2020 ). This complication has been observed in 0.0–92.1% patients treated with FCM (18 studies), 0.0–40.0% treated with iron sucrose (5 studies), 0.4% treated with ferumoxytol (1 study), and 0.0% treated with low-molecular-weight iron dextran (1 study).…”
Section: Discussionmentioning
confidence: 99%
“…Ferric carboxymaltose (FCM) is an iron formulation increasingly prescribed due to its effectiveness and fast infusion time. FCM can cause hypophosphatemia secondary to fibroblast growth factor 23 (FGF23) dysregulation ( Glaspy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypophosphataemia rates were found to be 0.0–92.1% for FCM, 0.0–40.0% for iron sucrose, 0.4% for ferumoxytol and 0.0% for low-molecular-weight iron dextran. 31 All of the RCTs in the systematic review reported hypophosphataemia to be transient, while the case reports included (exclusively involving FCM) described severe fatigue associated with acute hypophosphataemia and osteomalacia and fractures in cases of chronic hypophosphataemia linked to repeated i.v. iron infusions.…”
Section: Iron Metabolism and Phosphate – What Is The Linkmentioning
confidence: 99%